Recent advances in the roles of exosomal microRNAs (exomiRs) in hematologic neoplasms: pathogenesis, diagnosis, and treatment - Faride Nam Avar Jahromi; Razieh Dowran; Reza Jafari (Cell Communication and Signaling, 2023)
Abstract In clinical diagnosis, the capability of exosomes to serve as biomarkers is one of the most important biological functions of exosomes. The superior stability of exosome biomarkers makes them superior to those isolated from traditional samples such as serum and urine. Almost all body fluids contain exosomes, which contain proteins, nucleic acids, and lipids. Several molecular components of exosomes, including exosome proteins and microRNAs (miRNAs), are promising diagnostic biomarkers. These exosomes may carry genetic information by containing messenger RNA (mRNA) and miRNA. The miRNAs are small noncoding RNAs that regulate protein-coding genes by acting as translational repressors. It has been shown that miRNAs are mis-expressed in a range of conditions, including hematologic neoplasms. Additionally, miRNAs found within exosomes have been linked with specific diseases, including hematologic neoplasms. Numerous studies suggest that circulating exosomes contain miRNAs similar to those found in parental cancer cells. Exosomes contain miRNAs that are released by almost all kinds of cells. MiRNAs are packaged into exosomes and delivered to recipient cells, and manipulate its function. It has been recognized that exosomes are new therapeutic targets for immunotherapy and biomedicine of cancers. The current review discusses the current evidence around exosomal miRNAs involved in the pathogenesis, diagnosis, and treatment of hematologic neoplasms. Video Abstract